(untitled) (Analysis of International Sciences, 2023)
Due to the increasing role of information technologies in the life of society in Uzbekistan, rapid informatization and computerization of the education sector is being observed. Advanced systems and innovative technologies aimed at raising the quality of education to a new level are being actively introduced. This scientific article provides information on the advantages of smart technologies.